Produção de enzimas ?-amilase por Aspergillus niger em fermentação no estado sólido utilizando bagaço de malte de cevada - Lima, Renan Carlos Freitas de (2019)
The objective of the present work was to present an alternative for the production of a-amylase enzymes by Aspergillus niger fungus through solid-state fermentation. The solid residue of the brewing industry, the brewer’s spent grain, was used as the fermentation substrate combined with an inert support of sugarcane bagasse. In order to characterize the fermentation substrate, analyzes of water, protein, lipids, carbohydrates, ashes and phosphorus, calcium, magnesium and potassium were realized. For the solid-state fermentation, a study was performed using an experimental of Central Composite Rotational Design (CCRD) in order to determine the best conditions of the enzymatic activity varying the solid matrix moisture (60 to 85%), the time (48 to 168 hours) and the percentage of substrate in the solid matrix (50 to 90%). Fermentation kinetics were performed to validate the values obtained by the experimental design. The effect of pH on the enzymatic activity was evaluated by extracting the enzyme complex in the pH range between 4.0 and 9.0, besides evaluating the stability of the enzyme with storage time of 24 and 48 hours after the extraction. The hydrolysis of the soluble starch was optimized by the action of the enzymes extracted by the DCCR method, varying the temperature factors (50 to 80 ºC) and the hydrolysis time (5 to 30 min). The characterization of the solid residue composition of the brewing industry presented a protein content of 16.13 ± 0.15 % and carbohydrate contents of 70.58 ± 0.97 %, qualifying as a promising residue with excellent sources of substrates for fermentation in solid state. The kinetics of amide hydrolysis by a-amylase were performed at different concentrations of substrate (0, 5, 7.5, 10, 20, 30, 40 and 50 g/L) to determine the Michaelis-Menten constant (Km) and the maximum speed (Vmax). The optimal conditions for solid state fermentation were 80% moisture, 102.1 hours fermentation and 85.9% substrate, obtaining 618.20 U/gMS. The optimum data for a-amylase production were validated, obtaining a value of 622.25 ± 33.76 U/gMS. The pHs of 4.0 and 4.5 presented higher activity with values of 1454.9-1421.2 U/gMS, respectively. After storage for 24 hours and 48 hours a-amylase activities reduced on average 4.57% and 10.43%, respectively. In the a-amylase hydrolysis process, the temperature and time variables had optimal conditions of 68 °C and 5 min, respectively, with a maximum enzymatic activity of 2699.22 U/gMS. The values of Km = 5.60 g/L and Vmax = 1.216 µmol/mL/min were determined by enzymatic kinetics.